A case of pulmonary arterial hypertension with chronic hepatitis that resulted in hepatosplenomegaly after administration of prostaglandin I2. Issue 5 (May 2020) - Goten, Chiaki; Usui, Soichiro; Hamaoka, Takuto; Harada, Tomoya; Inoue, Oto; Okada, Hirofumi; Takashima, Shin-ichiro; Kato, Takeshi; Murai, Hisayoshi; Sakata, Kenji; Furusho, Hiroshi; Kawashiri, Masa-aki; et al.
Abstract: The prognosis of pulmonary arterial hypertension (PAH) has significantly improved over the past two decades due to advances in medications, including pulmonary vasodilators. However, the side effects of these drugs remain problematic in some patients. A 51-year-old woman with chronic hepatitis C was diagnosed with PAH 7 years before presenting to our hospital. She was unable to continue her treatment with pulmonary vasodilators due to various side effects. She had a World Health Organization functional class of IV and was started on continuous infusion of prostaglandin I2 (PGI2). This therapy improved her symptoms, including dyspnea and fatigue. However, she began to complain of abdominal distension after 4 months of PGI2 therapy. Computed tomography showed significant hepatosplenomegaly. Her abdominal distension improved slightly after decreasing PGI2 treatment, but her dyspnea on exertion was exacerbated. She died 12 years after diagnosis of PAH due to uncontrollable heart failure. Here, we describe a rare case of PAH with hepatosplenomegaly after administration of PGI2. <Learning objective: Intravenous continuous prostaglandin (PG) I2 therapy is useful for the treatment of severe pulmonary arterial hypertension (PAH). However, it has numerous side effects that are difficult to control. We report a rare case of PAH with chronic hepatitis C that resulted in hepatosplenomegaly after PGI2 administration. In cases of chronic liver disease, it is important to keep in mind that administration of PGI2 may result in hepatosplenomegaly.>